Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, dan Pelayanan KPP terhadap Kepatuhan Wajib Pajak di Kantor Pelayanan Pajak Pratama Jakarta Senen Tahun 2025 - Teuku Tharmizi; Safri Nurmantu (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to analyze the influence of taxpayer knowledge, taxpayer awareness, and tax office services on taxpayer compliance at the Jakarta Senen Primary Tax Office in 2025. The research method uses a quantitative approach with multiple linear regression analysis. Data were collected through the distribution of questionnaires to taxpayers, with six statement items for each variable. The results show that taxpayer knowledge positively affects compliance by 26.9%. Taxpayer awareness contributes 64.3%, while tax office services contribute 69.8%. Simultaneously, these three variables explain taxpayer compliance by 73.4% (R Square = 0.734). This research is expected to provide input for the Jakarta Senen Primary Tax Office in improving service strategies and taxpayer education to strengthen tax compliance. Keywords: Taxpayer Knowledge; Taxpayer Awareness; Tax Office Services; Taxpayer Compliance